Development of a military mental health training program aiming to promote mental health and operational readiness in the Danish armed forces: an intervention mapping approach - Kjærgaard, Anders; Karstoft, Karen-Inge; Schmidt, Bjarke Wæhrens; Kirk, Jeanette Wassar (Frontiers in Public Health, 2025)
Mental health and operational readiness are essential to soldiers’ ability to perform under pressure. Yet within military systems, the mental domain has often been overlooked or insufficiently integrated into formal training structures. Although international programs have aimed to enhance mental health literacy and resilience among service members, evidence regarding their applicability across national contexts remains limited. This is the first comprehensive mental health training program that has been developed or evaluated in Denmark. This paper addresses that gap by outlining the development of Military Mental Training, the first tailored program designed to promote mental health and psychological stress management skills and long-term operational effectiveness among personnel. We used the Intervention Mapping framework to construct the program. This involved a systematic six-step process, including stakeholder input, needs assessment, performance and change objectives, and evidence-based components such as stress management techniques and psychoeducation components about stress, mental health and coping. The program offers a contextually adapted, theory-driven approach to strengthening soldiers’ mental health literacy and coping capacities from the earliest stages of military training that move beyond implicit assumptions and toward structured, culturally adapted and theory-informed approaches. As such, this paper offers a replicable roadmap for other Defense organizations seeking to embed psychological readiness more explicitly into core training structures. However, further research is needed to assess results of the program in terms of acceptability, feasibility, and long-term effectiveness in real-world military settings. Beyond its military application, the training provides soldiers with transferable skills for managing stress in both service and civilian life.